High-level stakeholders? insights on readying Australia for Next Generation Broadband - Mason, Claire; O’Brien-McInally, Beth; Dane, Sharon (Journal of Telecommunications and the Digital Economy, 2014)
We interviewed 24 high-level representatives from across Australian society and industry to explore (a) what changes might occur in each sector once next generation broadband (NGB) is widely available and (b) what action is needed to prepare for these changes. Most participants expected NGB to have a positive and profound effect on business and daily life in Australia. However, Australian organisations had been slow to engage with the opportunities offered by NGB. They were also concerned that certain groups could get left behind through digital divide. They called for government to better articulate the role of NGB in supporting Australia’s future social and economic prosperity, to act as a front-runner in the use of the new technology and to deliver policy addressing barriers to uptake. Leadership was also needed from public and private organisations, both to build the nation’s digital capability and in utilising NGB to transform business processes.